Spinal range of motion and plantar pressure in sport climbers - Hawrylak, A.; Chromik, K.; Ratajczak, B.; Barczyk-Pawelec, K.; Demczuk-Wlodarczyk, E. (Acta of Bioengineering and Biomechanics, 2017)
Purpose: The aim of the study was to investigate the range of motion (ROM) of lumbar and thoracic articulations and static and dynamic plantar pressure in sport climbing athletes. Methods: The sample included 30 sport climbers with a minimum of 2 years training experience and 30 physical education students who served as an active untrained control. ROM was assessed by a Saunders digital inclinometer and plantar pressure by a baropodometric platform. Results: Mean spinal ROMs were greater in the sport climbers with an exception of extension, rotation, and lateral thoracic flexion, with a high degree of statistical significance obtained in the majority of the analyzed ROMs. The climbers exhibited increased mean forefoot pressure (smaller rearfoot pressure) in both the dominant and nondominant extremities, with significant intergroup differences found in dominant forefoot/rearfoot pressure distribution. Conclusions: Sport climbers present increased lumbar and thoracic ROM. The characteristics of climbing may also affect transverse arch structure and plantar pressure distribution.